The International Survey of Family Law : 2019 edition - Brinig, Margaret F.; International Society on Family Law (Cambridge, United Kingdom : Intersentia, 2019)
The 'International Survey of Family Law' is the annual review of the International Society of Family Law. It brings together reliable and clearly structured insights into the latest and most notable developments in family law from all around the globe. Chapters are prepared by an international team of selected experts in the field, usually covering 20 or more jurisdictions in each edition. The International Society of Family Law (ISFL) is an independent, international, and non-political scholarly association dedicated to the study, research and discussion of family law and related disciplines. The Society?s membership currently includes professors, lecturers, scholars, teachers, and researchers from more than 50 different countries, offering a unique opportunity for networking within a truly international family law community.
"Published on behalf of the International Society of Family Law"--Page [ii].
Includes bibliographical references and index.
Keywords: Domestic relations; Domestic relations (International law); Family policy -- Europe